Askeri yargıda itaatsizlik suçları - Ulukanlıgil, Metin (My University, 2001)
Tez konumuz Askeri Yargıda İtaatsizlik suçlarıdır. Bu suçlar, emre itaatsizlik, emre itaatsizlikte ısrar, toplu asker karşısında veya silahlı iken yapılan itaatsizlik ve büyük zararlar veren itaatsizliktir. Tezimizin ilk bölümünde Askeri yargı, Askeri Kişi, Askeri Suç ve Sırf Askeri suç kavramlarına değinilmiş, yine aynı bölümde itaatsizlik suçlarının içinde geçen, hukuki terimler ayrıntılı olarak incelenmiştir. Tezimizin ikinci bölümünde ise itaatsizlik suçlarının unsurları incelenmiştir. Bu suçlar asker kişilerin ve asker kişi kabul edilen kişilerce işlenebilir. Bu suçlar sırf askeri suç kapsamındadır. Emre itaatsizlik suçları özel kanıtla işlenebilen suçlardan olup aranan kasıt ise maddi unsuru oluşturan fiilleri yapmaya yöneliktir. Bu suçlardan sadece emre itaatsizlik suçu ihmali hareketlerle de işlenebilir. Bu suçların maddi unsuru ise; sırasıyla üst veya amir tarafından verilen hizmete ilişkin emrin geç yapılması, eksik yapılması, değiştirilerek yapılması, hiç yapılmaması, yapmamakta ısrar edilmesi, bu itaatsizliğin toplu asker karşısında veya silahlı olarak yapılması, itaatsizlik sonucu büyük zararlar doğması fiilleri oluşturmaktadır. Söz konusu suçlar ani hareketli ve neticesi harekete bitişik suçlar olduğundan teşebbüs mümkün değildir. Müteselsil olarak işlenebilen suçlardır. İçtima mümkündür. Müeyyide olarak oda hapsi (emre itaatsizlik suçu için) ve hapis cezası öngörülmüştür. Sırf Askeri suç olmaları sebebiyle paraya çevrilemezler, ertelenemezler. Söz konusu suçlar seferberlikte ve savaş halinde işlenmesi durumunda faile verilecek ceza arttırılmaktadır. Sonuç bölümünde ise bu suça ilişkin değerlendirme ve önerilerimizi uygulamadaki aksaklıkları da göz önüne alarak sunduk.

Our thesis subject is about disobedience offence in Military Judgement. These offences are, disobedience to orders, insisting on disobedience to orders, disobedience in front of gathered soldiers or while armed, and disobedience that cause big damage. In the first part of our thesis we have pointed out the concepts of Military Judgement, Military person, Military offence and strict military offence, and in the same section, law terms in disobedience offence has been examined in detail. In the second part of our thesis, the components of disobedience offence has been examined ,These offences can be commited by military people,and people that are cosidered as a military person. These offences are within strict military offence. Order disobedience offences happen to be offences that can be commited with special proof of evidence and the purpose searched is towards doing the action that forms the materialistic component. From these offences, only neglience movement in order disobedience can also be manipulated. The materialistic component of these offences are as follows; a late reaction to a duty related order given by an upper rank or superior officer,orders done incomplete, given orders done changed, given order not done at all, insisting on not doing given orders, disobedience done in front of gathered soilders or while armed, and disobedience that cause big damage actions are formed. Because the subjective offences are similar to sudden act and the cosequence act offences, pozitivity is not possible. such offences can be commited in continuous succession. An assembly is possible. As a result, the punishment for disobedience offence is either room imprisonment or prison punishment and because these offences are strictly Military offences they cannot be turned to money or cannot be defered. In the position of the subjective offences commited during mobilization or war, the punishment will be increased. In the conclusion part, we have presented our evaluation adn the defects on applying our suggestions.
Keywords: Askeri ceza hukuku; İtaatsizlik